Psikoedukasi psychological first aid dan resiliensi pada ibu-ibu di Bantaran Kali Code Yogyakarta - Anggraeni, Dewi Soerna; Fatwasari, Astri; Wijaya, Dimas Adi; Utami, Narastri Insan (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2025)
This study aims to measure the effectiveness of psychoeducation based on Psychological First Aid (PFA) in improving the resilience of mothers living in Jogoyudan Village, along the banks of the Code River, Yogyakarta. The research employed a pre-test and post-test design to evaluate changes in resilience levels before and after the training, involving 6 mothers residing in the Code River area. The analysis results showed a significant difference in resilience scores between the pre-test and post-test, with a p-value of 0.027 (p < 0.05). These findings indicate that PFA-based psychoeducation effectively enhances resilience among mothers in the Code River area. Further analysis revealed that the more frequently PFA training was provided, the higher the levels of resilience achieved. This study offers significant practical contributions. PFA-based interventions can be implemented as an effective strategy to enhance resilience within the context of community empowerment. By incorporating this approach into community development programs, individuals, especially those living in disaster-prone areas, are expected to be better prepared to face life's challenges. This study recommends continuous PFA training to strengthen the psychological resilience of communities residing in high-risk environments.